2016
DOI: 10.5527/wjn.v5.i2.213
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in children and adolescents in Brunei Darussalam

Abstract: AIM:To determine epidemiology of Bruneian paediatric chronic kidney disease (CKD) patients and factors that affect growth and progression of disease. METHODS:A cross-sectional study conducted on all children below 18 years old who were diagnosed with CKD over a ten year period (2004 to 2013). The reference population was all children (< 18 years old) suffering from CKD and attending the tertiary paediatric nephrology clinic in Brunei Darussalam. Demographic (current age, age of diagnosis, gender, ethnicity), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…The estimated IKF prevalence of 4.9 (4.7–5.2)% in the CNNS sample amounts to around 49,000 (47,000–52000) cases per million population. Our estimates are similar to the prevalence observed in the Middle East and Southeast Asian countries [ 25 ]. Hospital-based epidemiological studies from Europe estimate the prevalence of pediatric CKD stages 2–5 between 30 and 100 per million age-related population.…”
Section: Discussionsupporting
confidence: 90%
“…The estimated IKF prevalence of 4.9 (4.7–5.2)% in the CNNS sample amounts to around 49,000 (47,000–52000) cases per million population. Our estimates are similar to the prevalence observed in the Middle East and Southeast Asian countries [ 25 ]. Hospital-based epidemiological studies from Europe estimate the prevalence of pediatric CKD stages 2–5 between 30 and 100 per million age-related population.…”
Section: Discussionsupporting
confidence: 90%
“…The global prevalence of paediatric CKD through screening programs has varied from <1-6%, [21][22][23][24], although our study reported higher prevalence (9.3%) compared to the published literature. However, a mass screening program in Korean school children with abnormal urinary findings depicted a CKD prevalence of 36.9% [25].…”
Section: Discussioncontrasting
confidence: 64%
“…Harambat et al reported that the exact prevalence of CKD stages 2–5 in the EU countries is not known and it depends on the country and ranges from 55–60 to 70–75 pmarp in Spain and Italy, as the disease at its early stages does not show any specific symptoms and is difficult to diagnose [ 5 ]. Meanwhile, in the Middle East (Kuwait) and Southeast Asia (Brunei Darussalam) countries, it is considerably greater and accounts for 329 and 736 pmarp, respectively [ 5 , 18 ]. According to the data by the Serbian Pediatric Registry of Chronic Kidney Disease, the prevalence of CKD stages 2–5 is 96.1 pmarp [ 19 ].…”
Section: Discussionmentioning
confidence: 99%